The Influence of Parental Verbal Abuse on The Self Confidence in Early Childhood - Putri, Tri Rahayu Argo; Zulkarnaen, Z (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aimed to explore the influence of parental verbal abuse on the self-confidence of early childhood children. Methodology: Using qualitative methods with a phenomenological approach, the research was conducted at Jatipurwo 2 Kindergarten in Karanganyar, involving group B children who experienced verbal abuse, as well as teachers as key inform-ants. Data collection techniques included in-depth interviews, participatory observations, and documentation, where interviews explored the children's direct experiences of verbal abuse, while observations and documentation supported data on their behavior and psychology. Analysis was performed using phenomenological methods and the Miles and Huberman procedures, which included data reduction, data presentation, and conclusion drawing. Results: The results showed that parental verbal abuse caused a significant decrease in children's self-confidence, marked by fear, an inability to interact with peers, and doubts in self-expression. Children who experienced verbal abuse tended to display closed emotional expressions and showed emotional de-pendence on their teachers. Teachers also observed behavioral changes in the children, including low participation in class activities. Applications/Originality/Value: These findings highlighted the importance of teachers in detecting and sup-porting children who experienced verbal abuse, as well as the need for pa-rental education to reduce negative verbal abuse behaviors.